2006
DOI: 10.1007/s00198-006-0225-8
|View full text |Cite
|
Sign up to set email alerts
|

COL1A1, ESR1, VDR and TGFB1 polymorphisms and haplotypes in relation to BMD in Spanish postmenopausal women

Abstract: Polymorphisms at COL1A1 and TGFB1 and haplotypes at COL1A1 and ESR1 were found to be associated with BMD in a cohort of postmenopausal Spanish women. Moreover, COL1A1 polymorphisms showed significant interactions among them and with the VDR 3' polymorphisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
1
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 37 publications
5
34
1
5
Order By: Relevance
“…There have been several association studies and meta-analyses of this SNP and its relation to BMD variations and vertebral fractures; furthermore, functional studies have shown that the T allele of this polymorphism is associated with effects on DNA binding, gene transcription, protein production, and defects in bone mineralization (Grant et al 1996;Efstathiadou et al 2001;Mann et al 2001;Wynne et al 2002;Mann and Ralston 2003;Stewart et al 2005;Bustamante et al 2007;Yazdanpanah et al 2007;Jin et al 2009Jin et al , 2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several association studies and meta-analyses of this SNP and its relation to BMD variations and vertebral fractures; furthermore, functional studies have shown that the T allele of this polymorphism is associated with effects on DNA binding, gene transcription, protein production, and defects in bone mineralization (Grant et al 1996;Efstathiadou et al 2001;Mann et al 2001;Wynne et al 2002;Mann and Ralston 2003;Stewart et al 2005;Bustamante et al 2007;Yazdanpanah et al 2007;Jin et al 2009Jin et al , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another polymorphism in the 5′ flank of COL1A1, rs1107946 (−1997G/T), was significantly associated with lumbar spine BMD and femoral neck BMD in a cohort of Spanish postmenopausal women (Garcia-Giralt et al 2002;Yamada et al 2005). However, the results of studies seeking associations of these polymorphisms with osteoporosis have not always been consistent in different population analyses (Wynne et al 2002;Hubacek et al 2006;Bustamante et al 2007;Yazdanpanah et al 2007;Jin et al 2009Jin et al , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Previously reported single nucleotide polymorphisms (SNPs) have small individual effects and the genetic correlation with the phenotypes is low (9). Therefore, more haplotype and gene-gene interaction cohort studies should be performed for the investigation of the genetic background of OP (5,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the incidence of OP is continuously increasing, and OP-related fractures have serous effects on the quality of life for many people. Gene polymorphisms may play an important role in the pathogenesis of this disease (Bustamante et al, 2007), and may be used as a diagnostic tool for early detection and prevention of OP (Wu, 2011).…”
Section: Introductionmentioning
confidence: 99%